First a priori Theoretical Evaluation of the Electroanalytical Cathodic Determination of Antibiotic Flavocillin - Volodymyr V. Tkach; Marta V. Kushnir; Viktor V. Kryvetskyi; Inna I. Kryvetska; Igor V. Kryvetskyi; Yana G. Ivanushko; Petro Yagodynets; Zholt O. Kormosh; José Inácio Ferrão da Paiva Martins (Orbital: The Electronic Journal of Chemistry, 2024)
For the first time, the possibility of flavocillin electrochemical determination, assisted by vanadium (III) oxyhydroxide has been evaluated. The electrochemical determination will be given by gradual reduction of both flavonyl and penicyllyl moieties in mildly acidic medium, close to neutral. The analysis of the mathematical model, correspondent to the reaction mechanism, confirms the efficiency of cathodic electrochemical process for flavocillin electrochemical determination.